MATLAB and simulink in mechatronics education - Albagul, Abdulgani; Khalifa, Othman Omran; Wahyudi, Martono (TEMPUS publications, 2005)
MATLAB software package has been assisting engineers to design and test system models for different fields of engineering. It provides a deep understanding of system parameters and how they affect its performance. Since it is a programming package, it can interact with other programming languages to provide engineers who use those languages the flexibility to run their codes within a MATLAB environment. Engineering students can build their model and test it before implementing it in the real process. This paper presents and describes some dynamic models and control systems for mechatronics engineering students using MATLAB and Simulink. Those models will be used as laboratory experiments to expose students to different topics and techniques in control engineering. This will enhance students' knowledge and make them familiar with the MATLAB environment